2013
DOI: 10.2147/copd.s28576
|View full text |Cite
|
Sign up to set email alerts
|

Ten years of tiotropium: clinical impact and patient perspectives

Abstract: Tiotropium bromide is an anticholinergic agent that has gained worldwide acceptance as a first-line, once daily maintenance therapy for patients with moderate-to-severe chronic obstructive pulmonary disease. The purpose of this review is to synthesize the evidence base in the past 10 years on the development of tiotropium and its efficacy compared to other able interventions such as long-acting beta agonists (LABAs), as well as to assess its safety profile and its effects on health-related outcomes in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
7

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 43 publications
0
24
0
7
Order By: Relevance
“…77 The use of the SoftMist® device was associated with increased overall mortality compared to subjects using placebo, LABA, or tiotropium via HandiHaler® (OR 1.51-1.63), and even higher cardiovascular mortality (OR 1.81). [78][79][80] The reason for increased mortality is not yet fully understood, but it is likely to be associated with greater systemic bioavailability, which was found to be dose dependent. On the other hand, a study by Wu YK et al has shown that 5 mcg via SoftMist® inhaler is not associated with significant change of HR variation after 3 months of therapy, compared to 18 mcg via Handihaler®.…”
Section: Tiotropiummentioning
confidence: 99%
See 1 more Smart Citation
“…77 The use of the SoftMist® device was associated with increased overall mortality compared to subjects using placebo, LABA, or tiotropium via HandiHaler® (OR 1.51-1.63), and even higher cardiovascular mortality (OR 1.81). [78][79][80] The reason for increased mortality is not yet fully understood, but it is likely to be associated with greater systemic bioavailability, which was found to be dose dependent. On the other hand, a study by Wu YK et al has shown that 5 mcg via SoftMist® inhaler is not associated with significant change of HR variation after 3 months of therapy, compared to 18 mcg via Handihaler®.…”
Section: Tiotropiummentioning
confidence: 99%
“…However, these findings should not affect the well-documented long-term safety on the use of tiotropium via Handihaler®. 82,78 …”
Section: Tiotropiummentioning
confidence: 99%
“…Сегодня препаратами 1 й линии терапии ХОБЛ являются длительно действующие бронходилата торы [6], среди которых наиболее изученным и наи более часто используемым является длительно дейст вующий антихолинергический препарат тиотропия бромид [64]. В многочисленных РКИ подтверждает ся положительное влияние тиотропия бромида на легочную функцию, улучшение клинических симп томов и качества жизни больных, повышение пере носимости физических нагрузок, снижение числа обострений ХОБЛ [64].…”
Section: длительная домашняя вентиляция легких (ддвл)unclassified
“…В многочисленных РКИ подтверждает ся положительное влияние тиотропия бромида на легочную функцию, улучшение клинических симп томов и качества жизни больных, повышение пере носимости физических нагрузок, снижение числа обострений ХОБЛ [64]. Кроме того, в открытых по пуляционных исследованиях, РКИ и метаанализах показан положительный эффект тиотропия бромида на прогноз у пациентов с ХОБЛ.…”
Section: длительная домашняя вентиляция легких (ддвл)unclassified
“…Препаратами 1 й линии тера пии у большинства пациентов с ХОБЛ являются длительно действующие (ДД) бронходилататоры (БД) [1], среди которых наиболее изученным и наи более часто используемым является действующий антихолинергический препарат (АХП) -тиотропия бромид [4,5].…”
Section: значение тиотропия для терапии хоблunclassified